Estudos sintéticos para a preparação do ácido 5-amino-4-oxopentanóico - Pereira, Douglas Eduardo Soares (2010)
In this work it was studied some methods for obtaining the 5-amino-4- oxopentanoic acid (ALA) and some of its derivates that could allow its easy preparation. This purpose would allow the use of these derivates in the studies of its photodynamic properties by another group of research in which we are joined to in this kind of work. There were selected for this study, paths of synthesis which could be accessible to the available conditions in our environment and could allow an easy and quick preparation of the ALA derivates proposed. Another aim was to turn around the use pressures above the atmospheric ones during the final step of reduction that demands the use a reactor. A literature proceeding previously studied that involved the reduction of metallic zinc has shown little selectivity, observing the reduction of other function groups besides those desired. The development of the intend proceeding involving the use of the Catalyses Transfer of Solid-Liquid Phase allowed the preparation of one of the ALA wanted derivates through a direct and quick proceeding. Such a proceeding involved in its final step the reduction of the preliminary formed ALAS, using a palladium catalyzer supported by a carbon and a hydrogenating equipment built in the lab that worked under atmospheric pressure. Nevertheless, the derivate so synthesized was obtained as mixture form due to the difficulties found during the final step of its purification.